Novel synthesis of 3-(Phenyl) (ethylamino) methyl)-4-hydroxy-2H-chromen-2-one derivatives using biogenic ZnO nanoparticles and their applications - G. C. Anjan Kumar; Yadav D. Bodke; B. Manjunatha; N. D. Satyanarayan; B. N. Nippu; Muthipeedika Nibin Joy (Chimica Techno Acta)
The present work describes the novel synthesis of 3, 3'-((phenyl) (ethylamino) methyl)-4-hydroxy-2H-chromen-2-one derivatives catalyzed by biogenic ZnO nanoparticles. The synthesized heterocyclic compounds were characterized by fourier-transform infrared spectroscopy (FT-IR), nuclear magnetic resonance (NMR) andmass spectrometric techniques. Absorption, distribution, metabolism and excretion properties and various toxicities (ADMET) studies and in silico molecular docking studies were carried out for the synthesized compounds. The synthesized compounds were screened for their efficacy towards the antioxidant activity and were subjected to corrosion inhibition study towards the mild steel in acidic medium by weight loss method. Additionally, the recyclability of the employed catalyst was studied.